A Study of Impact on the Socio-Economic Development in Changing Agricultural Land: Exploring the Interactions between Agricultural Practices, Socioeconomic Development, and Environmental Conservation (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Agricultural systems will have to respond to global change drivers such as population growth,changing dietary habits, and climate change. However, alterations of how food is produced in the futuremay conflict with other UN sustainable development goals, such as the protection of land resources andclimate change mitigation. To strike a balance between human demands and environmental implications,decision-makers must be aware of possible trade-offs between both objectives. and the research thatincluded agricultural marketing, brackish water fisheries' effects on socioeconomic development,agricultural land use, farming practices, fisheries in flood plains, and fisheries development.